Fingerprint of volatiles from plant extracts based on SPME-GC-MS - Siqueira,Ezequias P. (2007)
The Laboratory of Chemistry of Natural Products has an ex situ collection of extracts from organisms of the biodiversity aiming at bioprospecting. Nowadays the collection has about 4000 extracts from 1000 different species. Extracts are used to identify new bioactive compounds that could be useful for developing new drugs against neglected diseases like leishmaniosis, Chagas disease, malaria and tuberculosis. After biologic assays, the bioactive extracts need to be prepared in larger quantity to allow isolation and characterization of the bioactive component. At this time, it is important to not only confirm the bioactivity of new extract but also check if its composition is similar to the old one. It was evaluated the ability of Solid Phase Microextraction and Gas Chromatography-Mass Spectrometry analysis (SPME-GC-MS). It was used the AMDIS (Automatic Mass Spectral Deconvolution and Identification System) software as tools to collect and to compare the chromatographic profiles of each extract (fingerprint). Forty six samples were analyzed, it was possible to infer from the composition of each sample and common compounds. Nine groups of samples, collected at different time, were analyzed and seasonal modifications between then could be elucidated. The results showed that this methodology can be used to monitor the composition of extracts, allowing to monitor chemical changes that may occur during storage periods and to investigate the occurrence of a determined component in different extracts.